Does the Urinary Calcium/Citrate Ratio Add to the Diagnostic Workup of Children at Risk of Kidney Stones? A Cross-Sectional Study - Lee, Misan; Rodriguez Cuellar, Carmen Inés; Nagra, Ravneet; Wang, Zhan Tao Peter; Bhayana, Vipin; Filler, Guido (Journal of Child Science, 2019)
The purpose of the study was to evaluate urinary citrate/creatinine (UCi/UCr) and urinary calcium/citrate (UCa/UCi) ratios for distinguishing stone formers (SF) from non-stone formers (NSF) in an at-risk population. This was a retrospective study that included all pediatric patients who underwent urinary citrate testing from April 2017 to March 2018. The urinary levels of citrate, calcium, sodium, potassium, creatinine, oxalate, urate, pH, and specific gravity (SG) were measured in our clinical laboratory. Diagnosis of kidney stones was obtained through chart review.A total of 97 patients were included (46 NSF and 51 SF). The UCi/UCr ratio was not significantly different between NSF and SF. Median UCa/UCr ratio was higher in SF (0.67) compared with NSF (0.21, p < 0.0001). The median ratio of UCa/UCi was also higher in SF (1.30) than in NSF (0.65, p = 0.001). Oxalate, urate, pH, SG, and urinary sodium/potassium ratio did not differentiate between the SF and NSF. Positive correlation was seen between UCa/UCr and urinary sodium/creatinine UNa/UCr (p < 0.0001), as well as between UCa/UCr and UCi/UCr (p < 0.0001).The study has demonstrated significantly higher UCa/UCi and UCa/UCr in SF compared with NSF, while the use of urinary oxalate, urate, pH, and SG did not differentiate between SF from NSF. We also confirmed a positive correlation between UNa/UCr and UCa/UCr. While the utility of UCa/UCr is well established, our data suggest that UCa/UCi rather than UCi/UCr may be more predictive in the clinical setting when evaluating for nephrolithiasis.
Keywords: urinary calcium; urinary citrate; urinary creatinine; urinary oxalate; urolithiasis